ANALISIS PARTISIPASI PETANI TEMBAKAU DALAM GERAKAN PROTES SOSIAL PENOLAKAN PERATURAN PEMERINTAH NOMOR 109 TAHUN 2012 : STUDI KASUS PETANI TEMBAKAU DI KABUPATEN TEMANGGUNG - , SEKAR HERDIYANI, Drs. Bambang Sunaryo, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study discusses the social protest of tobacco farmers in Temanggung in order to reject âPP No.109 tahun 2012 tentang Pengamanan Bahan Yang Mengandung Zat Adiktif Berupa Produk Tembakau Bagi Kesehatanâ. History record that the emergence of social movements are an effective way to change unjust and unfair policies. Social protest in Temanggung born since 80s. Starting from the endless of pros cons tobacco issue, this condition is heightened when the government makes a PP 109/2012 which potentially threaten the survival of the tobacco farmers. Farmers move. This study uses quantitative methods. Researchers used purposive sampling method with the number of respondents 96 respondents who were tobacco farmers in Temanggung. Besides distributing questionnaires, researchers conducted in-depth interviews with informants related. From this study, it was found that the factor levels of economic status, education level, tenure status, political interest and political efficacy significantly influence participation rates of tobacco farmers in social protest. The social protest of tobacco farmers in Temanggung was able to make the government re-reviewing the rules that have been made previously. This is evidenced by the inclusion of RUU Pertembakauan on Legislation 2013.